2009
DOI: 10.1242/jeb.025767
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic model of the windlass mechanism of the foot: evidence for early stance phase preloading of the plantar aponeurosis

Abstract: In the present study we have estimated the temporal elongation of the plantar aponeurosis (PA) during normal walking using a subject-specific multi-segment rigid-body model of the foot. As previous studies have suggested that muscular forces at the ankle can pre-load the PA prior to heel-strike, the main purpose of the current study was to test, through modelling, whether there is any tension present in the PA during early stance phase. Reflective markers were attached to bony landmarks to track the kinematics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
127
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(136 citation statements)
references
References 25 publications
9
127
0
Order By: Relevance
“…Plantar fascia stretch generated a larger deformation so the stimulation on plantar fascia was supposed to be better. Meanwhile, the 1st ray of plantar fascia both had larger deformation than the rest four rays in two stretching simulation, which complies with previous research [24].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Plantar fascia stretch generated a larger deformation so the stimulation on plantar fascia was supposed to be better. Meanwhile, the 1st ray of plantar fascia both had larger deformation than the rest four rays in two stretching simulation, which complies with previous research [24].…”
Section: Discussionsupporting
confidence: 90%
“…Plantar fascia have been modelled as five rays corresponding to the order of five metatarsal. One special structure in plantar fascia model were four spheres locating beneath each metatarsal head which had contact with metatarsal so to simulate the interaction of plantar fascia with metatarsal in vivo [24]. Stiffness and damping ratio were defined according to previous researches [25].…”
Section: Multi-segment Foot Model Validationmentioning
confidence: 99%
“…1), according to Leardini et al (2007). Before starting the walking trials, in order to define the neutral position of the foot, a 1 s static acquisition was taken with the subject standing still in a right-leg support (Caravaggi et al, 2009), the left foot in contact with the floor but with minimum load, i.e. no-weight bearing for the analysed leg.…”
Section: Methodsmentioning
confidence: 99%
“…Perhaps most importantly, we can optimize muscle properties during rapid changes in speed and changes in incline in both running and walking (Lichtwark & Wilson 2006, 2007. We have suggested that increased stiffness results from pre-tension applied to the plantar aponeurosis (PA) by heel-strike or earlystance muscle activity (in triceps, tibialis anterior and the digital dorsiflexors; Pataky et al 2008;Caravaggi et al 2009). The windlass mechanism created as the PA wraps round the heads of the metatarsals (figure 1a) is known to contribute to stiffen the foot in late stance (Hicks 1954) by pulling on the calcaneus, causing inversion of the subtalar joint and hence 'locking' the midtarsal joint (Tansey & Briggs 2001).…”
Section: The Legacy Of Arboreal Origins For Human Bipedalitymentioning
confidence: 99%